Cosmogenic production rates and recoil loss effects in micrometeorites and interplanetary dust particles. (25th January 2013) - Trappitsch, Reto; Leya, Ingo
Abstract We present a purely physical model to determine cosmogenic production rates for noble gases and radionuclides in micrometeorites (MMs) and interplanetary dust particles (IDPs) by solar cosmic‐rays (SCR) and galactic cosmic‐rays (GCR) fully considering recoil loss effects. Our model is based on various nuclear model codes to calculate recoil cross sections, recoil ranges, and finally the percentages of the cosmogenic nuclides that are lost as a function of grain size, chemical composition of the grain, and the spectral distribution of the projectiles. The main advantage of our new model compared with earlier approaches is that we consider the entire SCR particle spectrum up to 240 MeV and not only single energy points. Recoil losses for GCR‐produced nuclides are assumed to be equal to recoil losses for SCR‐produced nuclides. Combining the model predictions with Poynting‐Robertson orbital lifetimes, we calculate cosmic‐ray exposure ages for recently studied MMs, cosmic spherules, and IDPs. The ages for MMs and the cosmic‐spherule are in the range <2.2–233 Ma, which corresponds, according to the Poynting‐Robertson drag, to orbital distances in the range 4.0–34 AU. For two IDPs, we determine exposure ages of longer than 900 Ma, which corresponds to orbital distances larger than 150 AU. The orbital distance in the range 4–6 AU for one MM and the cosmic spherule indicate an origin either in the asteroid belt or release from comets coming either from the Kuiper Belt or the Oort Cloud. Three of the studied MMs have orbital distances in the range 23–34 AU, clearly indicating a cometary origin, either from short‐period comets from the Kuiper Belt or from the Oort Cloud. The two IDPs have orbital distances of more than 150 AU, indicating an origin from Oort Cloud comets.